1991
DOI: 10.1021/bi00244a023
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Rev expressed in recombinant Escherichia coli: purification, polymerization, and conformational properties

Abstract: The high-level expression of HIV-1 Rev in Escherichia coli is described. Protein in crude bacterial extracts was dissociated from bound nucleic acid with urea. A simple purification and renaturation protocol, monitored by circular dichroism, is described which results in high yields of pure protein. The purified protein binds with high affinity to the Rev-responsive element mRNA and has nativelike spectroscopic properties. The protein exhibits concentration-dependent self-association as judged by analytical ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
113
2
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 84 publications
(128 citation statements)
references
References 39 publications
11
113
2
2
Order By: Relevance
“…Having these synthesis tools in hand, we plan to study the effect of post-translational modifications [54][55][56] on the function and structure of the Rev protein, along with introducing chemical switches [57,58] to control Rev folding and self-assembly, to better understand these processes on the function of Rev protein. [4,53,59] …”
Section: Expression Of Hiv-1 Revmentioning
confidence: 99%
See 2 more Smart Citations
“…Having these synthesis tools in hand, we plan to study the effect of post-translational modifications [54][55][56] on the function and structure of the Rev protein, along with introducing chemical switches [57,58] to control Rev folding and self-assembly, to better understand these processes on the function of Rev protein. [4,53,59] …”
Section: Expression Of Hiv-1 Revmentioning
confidence: 99%
“…The arginine-rich motif (ARM, residues 34-50) acts as the nuclear-localization signal (NLS) and as a binding site for the Rev response element (RRE), which is present in all incompletely spliced viral mRNAs. [3][4][5][6] Although Rev was discovered nearly three decades ago, [7] biochemical and structural studies aimed at understanding the structural and functional aspects of the Rev protein are still limited because of its strong tendency to oligomerize, aggregate, and precipitate. [4,8,9] As a result, the majority of the Rev studies have been performed on peptides derived from the protein sequence, and on Rev conjugates such as Rev-GFP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rev is a good target for antiviral therapies, since Rev is absolutely necessary for HIV-1 replication [27,28]. It has been shown that various organic compounds have the ability to target the Rev/RRE interaction [29].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that various organic compounds have the ability to target the Rev/RRE interaction [29]. Neomycin B, diphenylfuran cation, and proflavine are small molecules that can prevent Rev from binding to the RRE sequence [27,29,30]. If Rev is incapable of binding to the RRE on the pre-mRNA, the RNA will not be exported to the cytoplasm, also resulting in lack of necessary structural proteins.…”
Section: Introductionmentioning
confidence: 99%